STRATEGI GURU DALAM MENGEMBANGKAN KREATIVITAS SISWA PADA PEMBELAJARAN SENI TARI DI SMA NEGERI 3 PAYAKUMBUH - Pebrina Dewika; Yuliasma Yuliasma; Zora Iriani (SENDRATASIK UNP, 2013)
Abstract This article aimend at describing strategies which were used by teacher to develop students’ creativities at SMA Negeri Payakumbuh. The design of this research was qualitative. The method used was the descriptive method. The objects of this research were strategies applied by teachers in the learning process of dancing. The main instrument of the research was the researcher. The data were obtained from observation, interview, and literature review. They were analyzed by using the phenomenology technique. Based on the data analysis, it was found that there were variouseffective strategies in learning dancing such as giving lectures question and answer, providing the students with demonstration, and cooperative learning method. These strategies developed the students’ creativities well. It was seen from students’ creative imagination in developing the basic moves of Tari Rantak. Besides, the use of appropriate audio visual media also stimulated the students so that their learning motivation became higher as well as provided them with new experiences to advance the learning processes. Keywords: Teachers’ Strategies, Learning Dancing,  Students’ Creativities